THE MOJOARUM SITE AS A SOURCE OF IDEAS FOR CREATING BATIK MOTIFS FOR KEBAYA CLOTHES - Desiatri, Olivia Evi; Oktaviani, Danissa Dyah (Runtas : Journal Of Arts And Culture, 2024)
This study aims to make Mojoarum Site as a source of inspiration in creating batik motif for Javanese blouse. The artwork creation process begins with exploration stage by doing direct observation toward Mojoarum site. The results of the observations are then used as a batik motif on Javanese blouse. Designing process is the next stage after exploration where, at this stage, the selection of the most suitable batik motifs is carried out. The last step is embodiment process in which this step uses covering and dying technique in creating batik motifs. Naphthol was chosen as coloring matter for resulting sense of beauty to the artwork. Overall, the embodiment process comprises nyorek (creating pattern), membatik (drawing batik motif), coloring, melorod (releasing wax from fabric), sewing, and finishing. This creation process resulted in four works and each one was named according to the history of the formation of the Mojoarum site as a village. The name of the first work is Slobog Paceklik, the second work is Udan Liris Bramantha, the third work is Sidomukti Sutrepta, and the fourth work is Sidomukti Rahayu Windraya. We then call the batik motifs relulted from this artwork creation as Mojoarum Batik Motif. It is expected that the society inspired to be more care with environment and tries to maintain cultural preservation through the creation of Mojoarum Batik Motifs.